Community Based Research: Generating Madani Society through Productive Habituation Patterns in the Month of Ramadhan Based on the Al-Qur'an and Sunnah - Muya Syaroh Iwanda Lubis; Rini Mardyani Florida; Devi Febrianti Putri; Dinda Farhani; Firda Zulaikha; Kinanti Nur Anjani; Rika Amilda (ASSUNNAH PRESS, 2023)
Madani's people can be defined as civilization society in building, living, and fulfilling his life. Madani society will happen when a society properly applies the principles of democracy, and the purpose of this activity is to form productive reforms in the society of children. In the Al-Qur'an itself, it is explained that the best people to form a more humanistic and tolerant human civilization